Cell surface changes in mouse peritoneal macrophages after induction with proteose peptone or thioglycollate - Vĕtvicka, V; Viklický, V; Zelený, V (Folia biologica, 1979)
Some five to six per cent of mouse PEC spontaneously form rosettes with SRBC. This weak intercellular interaction is most likely mediated by a "receptor" for SRBC located on the surface of peritoneal macrophages. Manifestation of the receptor is influenced by the genetic background and the H-2 haplotype of PEC donors; a high proportion of RFC is associated with the H-2s haplotype. PEC derived from intact mice markedly differ in morphological and functional characteristics from those of PP- or TG-pretreated donors. Formation of rosettes by induced macrophages depends on the time interval between stimulation and PEC harvesting and on the type of the inducing agent; it is also radiosensitive and more responsive to the action of colchicine. TG-induced macrophages have a significantly reduced capacity to bind syngeneic lymphoid cells. The difference in adhesivity between intact and stimulated PEC can be abolished by glutaraldehyde prefixation. In vivo induction results in modified morphological and functional properties of macrophages, including transformation of their cell surface.
Keywords: thioglykoláty; tvorba rozet; Gamma Rays; Rosette Formation; Colchicine; Ascitic Fluid; ascitická tekutina; Female; makrofágy; glutaraldehyd; záření gama; Cell Adhesion; Genotype; zvířata; histokompatibilní antigeny; myši; kolchicin; Caseins; Culture Media; Thioglycolates; Mice; kultivační média; Histocompatibility Antigens; Peptide Fragments; ženské pohlaví; Male; Glutaral; peptidové fragmenty; Mice, Inbred Strains; genotyp; Animals; buněčná adheze; Macrophages; mužské pohlaví; inbrední kmeny myší; kaseiny